Spatial dimension of macrophage heterogeneity in liver diseases - Adrien Guillot; Frank Tacke (eGastroenterology)
The structural and cellular organisation of the liver has unique features that define it as both a metabolic and an immunological organ. Noteworthy, liver resident macrophages, named Kupffer cells, represent the most frequent tissue resident macrophage population in the human body. Nonetheless, on acute or chronic tissue injury, Kupffer cells seem rather static and may undergo cell death, while the liver is massively infiltrated by circulating immune cells such as bone marrow-derived macrophages, also termed monocyte-derived macrophages, which drastically alter the hepatic immune landscape. Over the last decade, our knowledge on liver macrophage populations during homeostasis and liver diseases has greatly expanded. This particularly holds true in light of the recent fast-paced technological advances that brought novel dimensions to our knowledge, either in single-cell suspensions, in a two-dimensional plane or a three-dimensional space, or even in time-lapse (intravital) microscopy. This novel understanding goes from unravelling a previously underestimated macrophage diversity (eg, in terms of activation phenotype or cellular origins) to identifying spatially or temporally restricted responses that drive liver disease outcome. This review aims at providing insights into the most recent breakthroughs in our understanding of liver macrophage biology and its roles in liver (patho)physiology, in a four-dimensional perspective.